PELATIHAN WELAS ASIH DIRI BERKESADARAN UNTUK MENURUNKAN KECEMASAN MASA DEPAN PADA SENIMAN PEREMPUAN - Rahayu, Ni Luh Putu Diah Putri; Moordiningsih (JIP (Jurnal Intervensi Psikologi), 2026)
ABSTRACT: This study aimed to investigate the effect of mindful self-compassion training on future anxiety among female artists. A randomized pretest-posttest control group design was employed, involving 14 female artists in Bali who reported moderate to high levels of future anxiety. The participants were randomly assigned into two equal groups: an experimental group (n = 7) that received the mindful self-compassion training, and a control group (n = 7) that received no intervention. Data were collected using the Future Anxiety Scale developed by Al-Mashikhi. Data analysis using the Mann-Whitney U test revealed a significant difference between the experimental and control groups (Z = -3.137, p = .005). Furthermore, the Wilcoxon signed-rank test demonstrated a significant difference in anxiety scores before and after the intervention within the experimental group (Z = -2.371, p = .018). These findings indicate that mindful self-compassion training is effective in reducing future anxiety among female artists. Key words: Female artists, future anxiety, mindful self-compassion training.  ABSTRAK: Penelitian ini bertujuan untuk menguji pengaruh pelatihan welas asih diri berkesadaran terhadap kecemasan masa depan pada seniman perempuan. Desain eksperimen pretest-posttest control group digunakan dengan melibatkan 14 seniman perempuan di Bali yang memiliki tingkat kecemasan masa depan pada kategori sedang hingga tinggi. Seluruh partisipan dibagi secara acak ke dalam dua kelompok: kelompok eksperimen (n = 7) yang menerima pelatihan welas asih diri berkesadaran dan kelompok kontrol (n = 7) yang tidak diberi perlakuan. Instrumen yang digunakan adalah Future Anxiety Scale yang dikembangkan oleh Al-Mishikhi. Analisis data menggunakan uji Mann-Whitney menunjukkan perbedaan signifikan antara kelompok eksperimen dan kontrol (Z = -3.137, p = .005). Lebih lanjut, Uji Wilcoxon Signed Rank Test juga menunjukkan perbedaan signifikan skor kecemasan sebelum dan sesudah intervensi pada kelompok eksperimen (Z = -2,371 , p = .018). Hasil ini menunjukkan pelatihan welas asih diri berkesadaran efektif menurunkan kecemasan masa depan pada seniman perempuan.  Kata kunci: Kecemasan masa depan, pelatihan welas asih diri berkesadaran, seniman perempuan.